2020
DOI: 10.1021/acs.jpcc.9b06023
|View full text |Cite
|
Sign up to set email alerts
|

Defective Phosphorene as a Promising Anchoring Material for Lithium–Sulfur Batteries

Abstract: The lithium−sulfur battery, despite having considerable advantages, is still far from its practical applications, which is primarily caused by the dissolution of polysulfide clusters of lithium (LiPSs) into the electrolyte. Entrapping these LiPSs through integration of the anchoring material with the electrode is an effective approach to overcome this problem. In this study, density functional theory and ab initio molecular dynamics have been adopted to systematically examine the anchoring behaviors of two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…51 The potential applications of defective black phosphorene and blue phosphorene (β-phase of phosphorene) in Li-S batteries have also been proposed through theoretical calculations. 52,53 For arsenene, antimonene and bismuthene allotropes, Zhang et al predicted that all corresponding β phases with the buckled form are the most stable structures. 54 β-arsenene, β-antimonene and β-bismuthene have been testified to exist and successfully isolated from group-VA bulk crystals.…”
Section: Introductionmentioning
confidence: 99%
“…51 The potential applications of defective black phosphorene and blue phosphorene (β-phase of phosphorene) in Li-S batteries have also been proposed through theoretical calculations. 52,53 For arsenene, antimonene and bismuthene allotropes, Zhang et al predicted that all corresponding β phases with the buckled form are the most stable structures. 54 β-arsenene, β-antimonene and β-bismuthene have been testified to exist and successfully isolated from group-VA bulk crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Defects are thought to have important effects on the electronic structure and electrochemical applications of Xenes. [123,124] Different synthetic methods could induce the different degree of defects in the Xenes. [125,126] Element doping is another important route to induce the formation of defects into the emerging Xenes.…”
Section: Tunable Electronic Band Structurementioning
confidence: 99%
“…The increasingly prominent climate changes and limited availability of fossil fuel issues have stimulated a tremendous amount of research interest in highly efficient and clean energy storage and conversion devices [1][2][3][4][5]. The development of new classes of advanced two-dimensional (2D) layered materials, including graphene, MoS 2 , phosphorene, have promoted tremendous technological progress in those energy resources (e.g., supercapacitor, different-type metal ion batteries (MIBs)), which are attributed to their extraordinary properties [2,[6][7][8][9][10][11][12][13][14][15][16][17]. The enhancement in the performance of these devices by incorporating layered materials indicated that the 2D materials commonly possess the following two unique characteristics:…”
Section: Introductionmentioning
confidence: 99%